PENERAPAN MODEL INKUIRI DALAM PEMBELAJARAN MENYUSUN TEKS EKSPOSISI SISWA KELAS VII SMP NEGERI 2 TAMAN SIDOARJO: PENERAPAN MODEL INKUIRI DALAM PEMBELAJARAN MENYUSUN TEKS EKSPOSISI SISWA KELAS VII SMP NEGERI 2 TAMAN SIDOARJO - Nia Farikhah; Agung Pramujiono (Buana Bastra, 2015)
The purpose of this study is that it is easy for students to write an exposition text through the inquiry learning model. The researcher applies an inquiry learning model that is applied to class VIIG students of SMP Negeri 2 Taman Sidoarjo. The research uses the application of a learning model, namely the application of inquiry. This learning model helps students to solve problems in groups in order to foster a sense of kinship and cooperation. Learning to write exposition texts was chosen as the study material because the students' ability to write exposition texts has not been achieved. This is based on learning outcomes that have not reached the expected KKM. From the initial observations, it was obtained that the pretest (before the inquiry model was applied) was 27.8% or 10 students who could compose the exposition text well or scored above the KKM and the posttest results (after the inquiry model was applied) 22.3% or 8 students had not. reach KKM. This research is a descriptive quantitative research in its implementation through two cycles, namely pretest and posttest. The pretest was carried out without using a learning model and the posttest was carried out with a learning model. Each cycle includes planning, implementation, observation, and reflection. The subjects of this study were class VIIG students of SMP Negeri 2 Taman Sidoarjo. The data collection of this research was carried out by observing the teacher and students to find out the activities of the teacher and students during the learning process, the students' writing learning outcomes to determine the improvement of learning outcomes.